Factors affecting ultraviolet-A photon emission from β-irradiated human keratinocyte cells. (3rd August 2015) - Le, M; Mothersill, C E; Seymour, C B; Ahmad, S B; Armstrong, A; Rainbow, A J; McNeill, F E
Abstract: The luminescence intensity of nm photons emitted from HaCaT (human keratinocyte) cells was investigated using a single-photon-counting system during cellular exposure to 90 Y β -particles. Multiple factors were assessed to determine their influence upon the quantity and pattern of photon emission from β -irradiated cells. Exposure of cells/5 mL to 703 μ Ci resulted in maximum UVA photoemission at counts per second (cps) from live HaCaT cells (background: 1–5 cps); a 16-fold increase above cell-free controls. Significant biophoton emission was achieved only upon stimulation and was also dependent upon presence of cells. UVA luminescence was measured for 90 Y activities 14 to 703 μ Ci where a positive relationship between photoemission and 90 Y activity was observed. Irradiation of live HaCaT cells plated at various densities produced a distinct pattern of emission whereby luminescence increased up to a maximum at cells/5 mL and thereafter decreased. However, this result was not observed in the dead cell population. Both live and dead HaCaT cells were irradiated and were found to demonstrate different rates of photon emission at low β activities (⩽400 μ Ci). Dead cells exhibited greater photon emission rates than live cells which may be attributable to metabolic processes taking place to modulate the photoemissive effect. The results indicate that photon emission from HaCaT cells is perturbed by external stimulation, is dependent upon the activity of radiation delivered, the density of irradiated cells, and cell viability. It is postulated that biophoton emission may be modulated by a biological or metabolic process.